ERROR ANALYSIS IN COMPOSITION WRITTEN BY NURSING DEPARTMENT STUDENTS OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Agustina, Noor Qomaria (Journal of Foreign Language Teaching and Learning, 2016)
There is more freedom nowadays for workers to move across border. One of the promising oppor- tunities is to become an overseas nurse. However, to become an overseas nurse, one needs a certain level of language skills; thus, it is important to embed English, as the world?s lingua franca, in the nursing science course. When the students of the Nursing Department master the English, they will be able to engage in a communication with others within the international scope. It is very important to prepare them with standard, error-free English to prepare them entering the global market. This research tries to figure out the students? language proficiency by viewing their gram- matical errors especially in the S-V agreement. The data were taken from the composition written by Nursing Department students, which were then analyzed using the concordance program, namely SCP 4.05. Using the seven pronouns (I, we, you, they, he, she, it) as the key words, the sentence contexts were examined. Then, the sentences that contain errors were taken and categorized. From this research, there are 5 kinds of students? problems reflected in the errors. They are: 1) sentence without verb, 2) errors in the use of be and stem, 3) inflectional ?s for the third singular person, 4) modals, and 5) auxiliary verb.